Remote meta‐C–H Cyanation of Arenes Enabled by a Pyrimidine‐Based Auxiliary. (6th September 2017) - Bag, Sukdev; Jayarajan, Ramasamy; Dutta, Uttam; Chowdhury, Rajdip; Mondal, Rahul; Maiti, Debabrata
Abstract: An easily removable pyrimidine‐based auxiliary has been employed for the remote meta ‐C−H cyanation of arenes. The scope of this Pd‐catalyzed cyanation reaction using copper(I) cyanide as the cyanating agent was demonstrated with benzylsilanes, benzylsulfonates, benzylphophonates, phenethylsulfonates, and phenethyl ether derivatives. The method was utilized for the synthesis of pharmaceutically valuable precursors. Abstract : Langer Arm : Eine Pyrimidin‐basierte dirigierende Gruppe (DG) steuert die meta ‐C‐H‐Cyanierung von Arenen mit Kupfer(I)‐cyanid. Die Brücke zwischen dem reagierenden Arenring und der Pyrimidinfunktion kann Silyl‐, Sulfonat‐, Phosphonat‐ und Ethermotive enthalten.